2018
DOI: 10.1007/s12035-017-0866-y
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Brain-Derived Neurotrophic Factor as a Biomarker of Alzheimer’s Disease: Are There Methodological Biases?

Abstract: Mounting evidence that alterations in brain-derived neurotrophic factor (BDNF) levels and signaling may be involved in the etiopathogenesis of Alzheimer’s disease (AD) has suggested that its blood levels could be used as a biomarker of the disease. However, higher, lower, or unchanged circulating BDNF levels have all been described in AD patients compared to healthy controls. Although the reasons for such different findings are unclear, methodological issues are likely to be involved. The heterogeneity of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 153 publications
1
40
1
Order By: Relevance
“…Thus, our method based on global recommendations aiming to improve and maintain health in older adults may not have been sufficiently intense in some participant to induce a significant effect on plasma BDNF production [24,28,61]. Several additional factors can however influence the basal synthesis of BDNF at the individual level such as genetic variation, metabolic disorders, and/or inflammatory process and hence the BDNF response to aerobictype training [62]. For example, some authors consider AD as a metabolic disorder mediated by insulin-resistance at the brain level [63].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our method based on global recommendations aiming to improve and maintain health in older adults may not have been sufficiently intense in some participant to induce a significant effect on plasma BDNF production [24,28,61]. Several additional factors can however influence the basal synthesis of BDNF at the individual level such as genetic variation, metabolic disorders, and/or inflammatory process and hence the BDNF response to aerobictype training [62]. For example, some authors consider AD as a metabolic disorder mediated by insulin-resistance at the brain level [63].…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of various substances in saliva may reflect their abundance in the brain more precisely than is the case for those measured in blood [40,41]. Blood BDNF passes from the brain through the blood-brain barrier, and therefore alterations in blood the BDNF level may be associated with disease pathology [42]. A previous study has indicated that the level of BDNF in the brain is correlated with its expression in the salivary gland via the blood [3].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show peripheral BDNF is related to numerous brain disorders. A recent meta-analysis finds that lower levels of peripheral BDNF are associated with an increased risk of depression (Brunoni et al, 2008 ), Alzheimer's disease (Balietti et al, 2018 ), Parkinson's disease (Rahmani et al, 2019 ), and strokes with an unfavorable outcome (Xu et al, 2018 ). There have been attempts to provide external BDNF, but this has not been successful (Houlton et al, 2019 ) due to poor blood–brain barrier permeability and short therapeutic half-life (Poduslo and Curran, 1996 ).…”
Section: Introductionmentioning
confidence: 99%